Topsy turvy in the line of fire - Chattopadhyay, Abira; Das, Asish Kumar; Burman, Subhasish; Hossain, Arif; De, Nayana; Sikarwar, Sweta (International Journal of Research in Medical Sciences, 2024)
In literature there are several schools of thoughts regarding the tooth present in line of fracture. Some supports the preservation to tooth and others in contrast against to the preservation of the tooth. A case of mandibular fracture with a tooth in the fracture line is presented in this paper. Removal of tooth done followed by reduction under G.A with 1 month postoperative follow-up. Different authors supporting different treatment plan for tooth in fracture line. It depends on case whether to remove the tooth or preserve. There are several pro and cons for both the treatment plan discussed in this paper.